On Finite Memory Universal Data Compression and Classification of Individual Sequences - Ziv, J. (IEEE transactions on information theory, 2008)
Consider the case where consecutive blocks of letters of a semi-infinite individual sequence over a finite-alphabet are being compressed into binary sequences by some one-to-one mapping. No a priori information about is available at the encoder, which must therefore adopt a universal data-compression algorithm. It is known that if the universal Lempel-Ziv (LZ) data compression algorithm is successively applied to -blocks then the best error-free compression, for the particular individual sequence is achieved as tends to infinity. The best possible compression that may be achieved by any universal data compression algorithm for finite -blocks is discussed. It is demonstrated that context tree coding essentially achieves it. Next, consider a device called classifier (or discriminator) that observes an individual training sequence . The classifier's task is to examine individual test sequences of length and decide whether the test -sequence has the same features as those that are captured by the training sequence , or is sufficiently different, according to some appropriate criterion. Here again, it is demonstrated that a particular universal context classifier with a storage-space complexity that is linear in , is essentially optimal. This may contribute a theoretical ldquoindividual sequencerdquo justification for the Probabilistic Suffix Tree (PST) approach in learning theory and in computational biology.